Health profile and care demands of children with special health needs - Lins, Maria da Paz Castelo; Oliveira, Ana Karoline Lima de; Leopoldo, Adelina Feitosa; Dimas, Denilson Ribeiro; Gonçalves, Jonas Loiola; Depianti, Jéssica Renata Bastos; Oliveira, Joseph Dimas de (Revista de Enfermagem da UFPI, 2024)
Objective: To identify the profile and clinical care demands of children with special health needs cared for by Primary Health Care teams in a city in the countryside of Ceará. Methods: A cross-sectional study with a quantitative approach, carried out in a Family Health Unit in the city of Tauá, Ceará, from May to December 2023. To identify children with special health needs (CSHCN), the Triagem de Crianças com Necessidades Especiais de Saúde instrument was applied to family members at home. Results: The majority of children were male (71.4%), preschoolers and schoolchildren (85.8%), students (82.1%), accompanied by their mother (82.1%), with family income greater than or equal to a minimum wage (60.7%) and living in urban areas (92.9%). The most significant demands were medication demands (85.7%) and development demands (85.7%), being perceived by family members/guardians or professionals in the age group of 1 to 3 years (39.3%). Of the 28 children, 89.3% have a diagnosis. It was observed that 60.7% have autism spectrum disorder (ASD), with six having a diagnosis of associated attention deficit hyperactivity disorder (ADHD). Conclusion: It was evident that health care is still mostly medical-centered on care for CSHCN treated in Primary Health Care.